Európai makroregionális stratégiák közlekedéslogisztikai célkitűzései - Veres, Lajos (Közép-Európai Közlemények, 2011)
The initiative of the European macro-regional strategies is a new dimension of the European regional cooperations, aiming to strenghten the European regional cohesion. The principle of the macro-regional control is to take down the responsibility to the lowest possibel level in order to reach better coordination and more efficient and more aligned measures. One of the thematic pillars of the macro-regional strategies is the increase of the accessibility and the attractiveness, which highlights the importance of the transport and the logistics. The experiences of the preparation of the Baltic Sea strategy and the European Danube regional strategy indicate that important new transport corridors appeared in the macro-regions and new regional cooperations emerge.